1994
DOI: 10.2337/diacare.17.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antecedent Hypoglycemia on Cognitive Function and on Glycemie Thresholds for Counterregulatory Hormone Secretion in Healthy Humans

Abstract: Our conclusions are as follows: 1) symptoms of moderate hypoglycemia occur at plasma glucose levels averaging approximately 5-15 mg/dl lower than the plasma glucose concentrations required to trigger counterregulatory hormone release; 2) after acute antecedent hypoglycemia, glucagon, EPI, and GH secretion occur at higher plasma glucose concentrations and NE is released at lower plasma glucose concentrations; and 3) there may be CNS adaptation to prior hypoglycemia reflected in preservation of logical memory fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…The finding of relatively preserved cognitive function after antecedent hypoglycemia agrees with previous data (14,15,25,26,36). On the other hand, several other studies (6,7,23) failed to reveal similar effects of recurrent hypoglycemia.…”
Section: Fruehwald-schultes and Associatessupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of relatively preserved cognitive function after antecedent hypoglycemia agrees with previous data (14,15,25,26,36). On the other hand, several other studies (6,7,23) failed to reveal similar effects of recurrent hypoglycemia.…”
Section: Fruehwald-schultes and Associatessupporting
confidence: 92%
“…The effect of antecedent hypoglycemia on hypoglycemic cognitive dysfunction has been discussed controversially thus far (21,22). Several studies (6,7,14,23) failed to detect any significant effects, whereas others (15,(24)(25)(26) indicated a preserving influence of antecedent hypoglycemia on cognitive function. The inconsistency appears to be related to methodical differences pertaining to the heterogeneity of the subjects studied, the small size of subject samples, and the cognitive function tests used.…”
mentioning
confidence: 99%
“…Cognitive dysfunction begins at lower blood glucose levels in people with type 1 diabetes and IHA compared with those with NHA (13), and antecedent hypoglycemia in individuals with type 1 diabetes and NHA can shift the thresholds for cognitive dysfunction to lower blood glucose levels (9,10,22,23). Glucose clamp studies in nondiabetic individuals have shown that 90 -150 min of hypoglycemia the day before cognitive testing attenuates the deterioration in short-term memory, reaction time, and auditory-evoked brain potentials (11,24,25), and avoidance of hypoglycemia can restore the glucose thresholds for cognitive dysfunction to higher levels (7,8,12). A previous, smaller study from our center compared the effects of hypoglycemia on cognitive function in 20 people with type 1 diabetes with either IHA or NHA and reported a trend toward poorer performance during hypoglycemia in IHA subjects (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the insulinoma patients studied by Mitrakou et al [15], and in intensively insulin-treated IDDM patients [5,11,13,16] antecedent hypoglycaemia was recurrent. In contrast, a single episode of hypoglycaemia lasting 56 h, was induced in non-diabetic subjects in the study by Boyle et al [9], whereas other studies induced only one episode of hypoglycaemia for only 2 h [8,17]. Despite these differences, all these studies do show at least some degree of downward shifting in glycaemic thresholds for cognitive dysfunction.…”
mentioning
confidence: 98%